Validation of the antibacterial effect of topically applied tranexamic acid using in vitro and in vivo models - Benjumea, Antonio; Díaz-Navarro, Marta; Gago-Campos, Ángela Sai; Visedo, Andrés; Hafian, Rama; Cercenado, Emilia; Sánchez-Somolinos, Mar; Muñoz, Patricia; Vaquero, Javier; Chana, Francisco; Guembe, María (Frontiers in Microbiology, 2024)
Background. Several studies have shown that tranexamic acid (TXA), an antifibrinolytic, reduces postoperative infection rates. Recent in vitro research showed that TXA alone and in combination with vancomycin and gentamicin had a synergistic effect against some staphylococcal strains. In the present study, this synergistic effect was validated in samples from patients with staphylococcal periprosthetic infection (PPI) and in an in vivo model.We tested 19 clinical strains (5 Staphylococcus aureus and 14 coagulasenegative staphylococci [CoNS]) against 10 mg/ml TXA alone and in combination with serial dilutions of vancomycin and gentamicin. The standardized microtiter plate method was used. The minimal inhibitory concentration (MIC) were calculated using standard visualization of well turbidity. We also used an S. aureus (ATCC29213) murine subcranial PPI model to compare the synergistic effect of TXA and gentamicin with that of TXA or gentamicin alone after 4 days of monitoring. The mice were euthanized, and discs were removed for analysis of cfu/ml counts and cell viability rate. Biofilm structure of both in vitro and in vivo samples was also analyzed using scanning electron microscopy (SEM).When TXA was combined with vancomycin or gentamicin, the MIC decreased in 30% of the strains studied. According to species, the MIC50 for vancomycin and gentamicin alone and in combination with TXA against S. aureus strains was the same. This was also the case for CoNS with vancomycin and its corresponding combination, whereas with gentamicin and TXA, a reduction in MIC50 was observed (2 dilutions). In addition, in the in vivo model, the mean (SD) log cfu/ml and cell viability rate obtained from the implant was lower in the group of mice treated with TXA and gentamicin than in those treated only with TXA or gentamicin. SEM images also corroborated our findings in strains in which the MIC was reduced, as well as the in the mice implants, with the area occupied by biofilm being greater in samples treated only with gentamicin or TXA than in those treated with TXA+gentamicin.We confirm that combining TXA with vancomycin or gentamicin exerts a synergistic effect. However, this only occurs in selected strains.